Educators as Content Creators in a Diverse Digital Media Landscape. Issue 1 (13th December 2021) - Paskevicius, Michael
This paper focuses on the ways educators can work within the guidelines of copyright while using digital media to develop educational content in legal and ethical ways by exploring several key contemporary trends in digital content creation. Educators need not create learning materials from scratch, as the pool of resources available via the internet, from educational publishers, or physically stored within schools serve as resources for the development of contextually relevant learning materials. Educators are increasingly becoming content creators, and with the development of digital literacies to support content creation, they can combine resources from multiple sources to meet the needs of their learners. This may be done to ensure a lesson is current, meet the needs of differentiated instruction and universal design for learning, to design learning materials that are engaging, and those that can be shared widely. In this digital media landscape, it is important for educators to know how to navigate digital media for use in developing curriculum or learning materials. By drawing on the digital literacies associated with copyright and open educational practices, educators can work within the guidelines of fair use, link and embed content, recognize and use openly licensed content, and explore resources from the public domain in legal and technically appropriate ways while developing learning materials. These approaches may impact educators' design processes, while also demonstrating and modelling to learners the creative ways one can remix and share resources found on the web.